Competitiveness of global agriculture: Policy lessons for food security - Jambor, Attila; Babu, Suresh Chandra (Springer, 2016)
From the IFPRI-produced synopsis: Jambor, Attila and Babu, Suresh Chandra. 2017. Competitiveness of global agriculture: Policy lessons for food security. Washington, D.C.: International Food Policy Research Institute (IFPRI). https://doi.org/10.2499/9780896292598